its impossible to solve with factoring for that one....
it the problem was y^4-10y^2+9=0.. that would be simple
(y^2-9)(y^2-1)=(y+1)(y-1)(y+3)(y-3)
for y^4-10y^2+9=0, the answer is 1,-1,3,-3
2007-11-14 14:42:12
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Are you sure that's not y^2 - 10y + 9? If so, the roots are 9 and 1.
Or should the second term be 10y^2? If so, factoring gives you (x^2 - 9)(x^2 - 1), and the roots are plus or minus 3 and plus or minus 1.
2007-11-14 22:47:08
·
answer #2
·
answered by historian 4
·
0⤊
0⤋
this equation can only be factored if it is y^4-10y^2+9=0
in this case the answer is...
(y^2-1)(y^2-9)
y=1, -1 or y=3, -3
2007-11-14 22:44:35
·
answer #3
·
answered by erin j 2
·
0⤊
0⤋
y^4-10y+9=0
roots:
y1 =1
y2 = 1.6608
and a pair of complex conjugate roots.
2007-11-14 22:49:28
·
answer #4
·
answered by Any day 6
·
0⤊
0⤋
about the only thing you could do is
(y-1)(y^3+y^2+y-9)=0
2007-11-14 22:42:56
·
answer #5
·
answered by info2know 3
·
0⤊
0⤋
(y^2-9)(y^2-1)
2007-11-14 22:45:29
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
(y-1)(y-9)
2007-11-14 22:40:30
·
answer #7
·
answered by DWRead 7
·
0⤊
2⤋